Associations between body mass index and the surgical phenotype and location of endometriotic lesions. Issue 5 (November 2021) - Enright, Katherine A.; Louise, Sandra; Dior, Uri P.; Healey, Martin; Holdsworth-Carson, Sarah J.
Abstract: Research question: Is there a relationship between body mass index (BMI) and endometriotic lesions, specifically surgical phenotype and lesion location? Design: An observational retrospective cohort study at the Royal Women's Hospital, Melbourne, Australia, including 471 histologically confirmed endometriosis patients. Statistical analyses included multivariate logistic regression and multivariate modelling, correcting for multiple testing. Outcomes were the presence or absence of surgically classified lesion phenotypes, as per revised American Society for Reproductive Medicine criteria including superficial or deep, peritoneal or ovarian, and adhesions (Study I); and lesions at specific anatomical locations (including pelvic side wall, uterosacral ligament, pouch of Douglas, ovarian, uterovesical fold, bladder, and pararectal endometriosis) (Study II). Results: In Study I, patients with higher BMI were more likely to have superficial peritoneal lesions (odds ratio [OR] 1.070, 95% confidence interval [CI] 1.004–1.144; P  = 0.044), and less likely to have deep ovarian lesions (OR 0.928, 95% CI 0.864–0.993; P  = 0.034). In Study II, patients with higher BMI were less likely to have uterovesical fold lesions (OR 0.927, 95% CI 0.867–0.985; P  = 0.021) or anterior compartment lesions (OR 0.940, 95% CI 0.888–0.989; P  = 0.023). After correcting for multiple testing, the relationship between BMI and lesion phenotypes did not persist ( P  > 0.01). Conclusions: This analysis does not conclusively support an influence of BMI on endometriotic lesion phenotype based on surgical classification or location. Further investigation of the physiological disturbances underlying BMI and the promotion of endometriotic lesion phenotypes and their location is warranted, but any effect is likely to be small.